Microwave-Assisted Synthesis and Spasmolytic Activity of 4-Indolylhexahydroquinoline Derivatives - El-Khouly, A.; Gündüz, M. G.; Çengelli, Ç.; Şimşek, R.; Erol, K.; Şafak, C.; Yıldırım, S. Öztürk; Butcher, R. J. (Drug Research, 2013)
In the present study a microwave-assisted one-pot method was applied for the synthesis of 18 novel condensed 1,4-dihydropyridines carrying the indole moiety. The compounds were achieved by the reaction of appropriate 1,3-cyclohexanedione, substituted indole carboxaldehyde derivative, alkyl acetoacetate and ammonium acetate in methanol, according to a modified Hantzsch reaction. The structure elucidation of the compounds was carried out by spectral methods including X-ray studies. Their spasmolytic activities through calcium channel blockade were assayed on isolated rat ileum. The obtained results indicated that the introduction of the brom atom on the indole ring altered the mentioned activity positively.
Keywords: hexahydroquinoline; indole; spasmolytic activity